OPTICAL MAMMOGRAPHY FOR CHARACTERIZING INTRINSIC CONTRAST OF BREAST CANCER AND ASSESSING RESPONSE TO NEOADJUVANT CHEMOTHERAPY - Anderson, Pamela. (2017)
Abstract: Near-infrared spectroscopy (NIRS) techniques are sensitive to absorption and scattering properties of biological tissue. NIRS and diffuse optical imaging have been applied to breast tissue for decades to exploit the high absorption of tumors resulting from their increased blood content. By developing methods focused on measuring the inherent contrast of tumors, optical imaging can be used to identify, characterize and monitor breast cancer. Optical images of the human breasts were collected in this work using a spectrally broadband (650-850 nm), continuous-wave, optical mammography instrument. A diffusion-based model was implemented to process the spectra measured through the breast to create maps of oxy-hemoglobin, deoxy-hemoglobin, water, and lipid concentrations. Oxygen saturation of hemoglobin was also mapped, which indicates balance between tissue perfusion and tissue metabolic rate of oxygen. The work in this thesis details the methods to characterize breast cancer contrast found on optical mammograms. Tumors (n = 26) exhibited increased hemoglobin and water concentrations as well as decreased lipid concentration and oxygen saturation of hemoglobin when compared to the surrounding healthy tissue. When considering the appropriate healthy tissue to which the tumor region should be compared against, a procedure was developed to provide a quantitative metric to evaluate the symmetry between a patient's right and left breast maps. The level of bilateral symmetry observed in the oxygen saturation of hemoglobin breast maps for healthy patients (n = 27) and patients with benign (n = 32) or malignant lesions (n = 21) was highest for healthy patients maps, although a high degree of variability was found. The use of optical mammography in assessing breast cancer response to neoadjuvant chemotherapy is also demonstrated. By obtaining optical mammograms on ten patients each time they received a chemotherapy infusion, the trends in the hemoglobin concentrations and oxygen saturation of hemoglobin were examined throughout the duration of treatment. The tumor pathologic response measured following surgical excision was then correlated to the optically measured trends. It was found that for patients achieving good response to treatment, the tumor oxygen saturation of hemoglobin experienced a significantly larger decrease compared to the tumors in poorer responding patients. Optical mammography has the potential to monitor patient response to treatment and guide clinical decision making.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Sergio Fantini.; Committee: Fiorenzo Omenetto, Darren Roblyer, and Roger Graham.; Keywords: Biomedical engineering, and Medical imaging.